PENGARUH PENGGUNAAN PASIR SILIKA DAN PASIR PANTAI TERHADAP KEKUATAN TARIK PADA PENGECORAN LOGAM ALUMINIUM - Utomo, Wahyu; Sari, Eli Novita; Fiveriati, Anggra; Wahid, Muhammad Abdul; Pamuji, Dian Ridlo (ELEMEN : JURNAL TEKNIK MESIN, 2024)
Casting is the process of manufacturing molten metal with a mold to produce a shape close to the original shape. The commonly used molding sand is mountain sand, river sand and silica sand. This research aims to analyze defects and tensile test results of castings with various types of sand (beach sand and silica sand) and types of aluminum (ADC 12 aluminum and aluminum from waste cans). The casting method used is traditional sand blasting. The results show defects in the form of surface hardness, rat tails, shrinkage cavities, and pinholes. The tensile test showed that the highest Ultimate Tensile Strength (UTS) value was obtained from a mixture of Al ADC 12 with beach sand with an average UTS value of 172.44 MPa.